Analisis Perbandingan Metode SAW, WP Dan TOPSIS Dalam Pemilihan Siswa Berprestasi Pada SDN Larangan 04 - Pari Purnaningsih; Ridwan Hakim; Satria Anggara Fayyadh Alwaly; Arich Herdiansyah; Perani Rosyani; Tri Widiayu Ningsih (CV. Multi Kreasi Media, 2023)
The selection of outstanding students at SDN Larangan 04 is carried out every year. This process is very important to improve the quality of student creativity in the learning process. In the selection stage students who excel will be selected from several specific criteria. The decision method determines the best alternative among several alternatives based on certain criteria, including the Weighted Product (WP) method, SAW and the TOPSIS method which have similarities with the ideal solution. Decision support system methods are compared to determine which method gives the highest score when selecting outstanding students. Comparison of the Weighted Product, SAW and TOPSIS methods shows that the Weighted Product method is more accurate than the SAW and TOPSIS methods in terms of sequence preference similarities with ideal solutions. Measured from the accuracy of the three methods, the WP (Weighted Product) method has the highest accuracy for determining student performance potential.